Advanced robotics and intelligent automation in manufacturing - Habib, Maki K., 1955- (Advances in computational intelligence and robotics (ACIR) book series., 2020)
"This book examines recent advances and state-of-the-art technologies in the field of robotics engineering and mechatronics for advanced intelligent manufacturing"--